Trabeculotomy in Primary Congenital Glaucoma - Riaz Ahmed Baloch, Abdul Qayyum (Pakistan Journal of Ophthalmology, 2014)
Purpose: To evaluate outcome and frequency of complications involved in Trabeculotomy in pediatric patients. Material and Methods: A total of 10 children were enrolled from Pediatric Ophthalmology Clinic, Bolan Medical College, Quetta during month of January and February 2013. Only Primary Congenital Glaucoma (PCG) patients were registered. Every patient had complete ocular examination under general anesthesia including anterior segment examination, measurement of intraocular pressure, corneal diameter, gonioscopy, axial lengths, fundoscopy and retinoscopy where possible. The success criteria was defined as: Intraocular pressure bellow < 15 mm Hg (under general anesthesia), simultaneous absence of cup: disc ratio progression, disproportional enlargement of cornea and stoppage or reduction in enhancement of axial length. Follow up period comprised of one, two, four & eight months respectively. Results: Ten patients under went trabeculotomy. Their mean age at the time of surgery was 15 months (range 10-29 months). The IOP was successfully controlled in 8 patients (80%). The pre-operative measurement was as follow: IOP 30 mm Hg (±5.7), horizontal corneal diameter 13.06 mm (±0.6), axial length 21.9 mm (±0.8), CDR was 0.52 (0.23). The final reading of various parameters was as under: IOP measured under GA 12 mm Hg, horizontal corneal diameter 13.0 mm (±0.5), Axial length 20.9 mm (0.6) and CDR was 0.3 (±0.21). 8 patients (80%) had successful surgery while 2 patients (20%) had unsuccessful surgery. 4 (40%) patients had complications comprising of false passage, Iris prolapse, stripes in descement‘s membrane and hyphaema. Conclusion: Trabeculotomy is highly successful procedure in primary congenital glaucoma. The complications observed were quite few in number. Distorted limbal anatomy of Buphthalmic eyes may affect prognosis of surgery. Some of the steps of trabeculotomy are similar to trabeculectomy. Key words: Trabeculotomy, Congenital glaucoma, Buphthalmos.